Oral Administration of Heat-Killed Mycobacterium manresensis Delays Progression toward Active Tuberculosis in C3HeB/FeJ Mice - Cardona, Paula; Marzo-Escartín, Elena; Tapia, Gustavo; Díaz, Jorge; García, Vanessa; Varela, Ismael; Vilaplana, Cristina; Cardona, Pere-Joan (Frontiers in Microbiology, 2016)
Low-dose tolerance using heat-killed mycobacteria has been tested as a means of stopping progression towards active tuberculosis (TB) lesions in a human-like murine model using C3HeB/FeJ mice. In the present study, we studied the effect of different treatment schedules with heat-killed non-tuberculous-mycobacteria (NTM) species when given orally, based on the hypothesis of generating oral tolerance. This study included M. manresensis, a new species belonging to the fortuitum group, present in drinking water. Oral treatment with M. manresensis for two weeks was able to induce a PPD-specific Tregs population, which has been related to a decrease in the neutrophilic infiltration found in TB lesions. Further mechanistic analysis using PPD-stimulated splenocytes links this two-week treatment with heat-killed M. manresensis to IL-10 production and memory PPD-specific Tregs, and also to a weak PPD-specific global immune response stimulation, increasing IL-6, TNF and IFN-γ production. In lungs, this treatment decreased the bacillary load, granulomatous infiltration and pro-inflammatory cytokines (TNF, IFN-γ, IL-6 and IL-17). Oral administration of M. manresensis during standard treatment for TB also significantly reduced the relapse of active TB after ending the treatment. Overall the data suggest that the use of heat-killed M. manresensis could be a new and promising tool for avoiding active TB induction and as adjunctive to TB treatment. This supports the usefulness of generating a new kind of protection based on a complex balanced immune response focused on both destroying the bacilli and including control of an excessive inflammatory response.